Edukasi Mitigasi Bencana Erupsi Gunung Kelud Menggunakan Media Audio Visual Gerak Dengan Motivasi Ibu Hamil - Dwi Ertiana; Taurisiawati Rahayu , Dewi; Cahyani, Niram (STIKES dan AKZI Karya Husada Kediri, 2025)
The use of motion audio visual media can increase interest and motivation for those who see it. The lack of interest and motivation of pregnant women in self-rescue for disaster mitigation, so it is necessary to educate pregnant women using motion audio visual media. The purpose of the study was to determine the relationship between education on disaster mitigation of the eruption of Mount Kelud using motion audio visual media and the motivation of pregnant women. The research design was a quasi-experimental study with One Group Pretest-Posttest. The population of 36 respondents was obtained by a sample of 33 respondents who were selected by simple random sampling. The study was conducted at TPMB Sri Utami, Asmorobangun Village, Puncu District, Kediri Regency, on May 12-17, 2024. The data collection process by providing a questionnaire as a pretest, respondents were given education about mitigating the eruption of Mount Kelud, then distributing questionnaires as a posttest, data analysis data editing, coding, scoring, and tabulating. The results of this study were tested using the Wilcoxon statistical test. The results of the study were obtained before the education was carried out, 100% had a moderate level of motivation. A posttest was carried out after education, 100% of respondents had high motivation. The results obtained indicate that there is a relationship between disaster mitigation education and the motivation of pregnant women. Before being given education, pregnant women have a moderate level of motivation, this is influenced by the low level of education. Low education affects the knowledge and thinking of individuals. So that individuals who have low knowledge need to be given repeated education so that they can continue to be motivated and encouraged to apply what is conveyed. The more education received, the higher the mother's motivation in saving herself from the eruption of Mount Kelud.